Blocks of ice and stone. Time and matter in Michelangelo's work - Navarro de Pablos, Javier; Martínez García-Posada, Ángel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
Through the ambiguous unfinished condition of certain of Michelangelo Buonarroti's works, this text explores his experiments with time and matter, taken as instruments of a conscious project. From an unknown ephemeral ice sculpture in the Palazzo Medici to his last work, the Rondanini Pietà, Michelangelo explores the limits of stone on a path that leads him from the perfection of polished marble to the abstraction of the rough block. A chronological record of his works reveals the infirmities of age, as if the sculptures were an extension of himself, from the adolescent face of the Vatican Pietà to the physical deformation of the series of Slaves in the tomb of Julius II. Centuries after his death, heritage dilemmas resound, such as the accommodation of the Rondanini in the Castello Sforzesco in Milan, which led to an initial project by the BBPR studio and a later relocation in which Álvaro Siza participated unsuccessfully, or the protection of the works of the Academy in Florence and the Pushkin Museum in Moscow during the Allied bombings of the Second World War by means of ephemeral systems that rescue the liminal condition of the works under construction. Through all these works, we continue to reflect from the present on the idea of the open work, which channels our architectural reflections on architecture, materiality and time.
Keywords: Michelangelo; non-finito; slaves; unfinished artwork; BBPR; Alvaro Siza